Greening of Public Transport in Pune – A Feasibility Study - Vasundhara Sen; Akanksha Hajela; G. Suneeth; Sarvesh Saxena; Ayush Deore (Australasian Accounting, Business and Finance Journal, 2023)
India's commitment to Electric Vehicles (EV) is a prime program furthering the country's achievement of Sustainable Development Goal (SDG) number 7. However, in spite of the much-needed policy push, EV adoption in India has been slow, both in private ownership and in public mobility. The average Indian commuter still depends heavily on public transport such as public buses, railways and rickshaws. Thus, the success of the EV transition in India lies in the speed with which e-vehicles can be developed and adopted in public transport solutions. This study assesses the feasibility of converting the public transport fleet (buses and 3 wheelers) into e-vehicles for the city of Pune. Pune records high per capita private vehicle ownership, resulting in high traffic congestion, traffic indiscipline issues and high vehicular fatalities. It is thus imperative that not only should public transport usage increase in the city, but it should also be electric, such that sustainability goals are achieved. This study presents a techno-economic analysis of greening Pune's public transport fleet. This paper begins with section 1, which introduces the EV landscape in India. Section 2 details the Total Cost of Ownership (TCO) framework, which evaluates financial costs associated with EVs in public transport fleets. Section 3 presents model results from the TCO analysis. Payback calculations are also presented to understand the minimum number of years to realise EV investment payback. Section 4 finally concludes this paper by presenting demand-side and supply-side interventions for a speedy EV transition for public transport fleets in Pune Metro Region.
Keywords: Green public transport; energy transition; electric vehicles; public transport transition; SDG 7; 3 wheelers; buses; India